Kinetic Studies on the Adsorption of Sungai Sireh Raw Water's Natural Organic Matters - Jusoh, Ahmad; Megat Mohd Noor, Megat Johari; Piow, See Boon (Universiti Putra Malaysia Press, 2001)
The presence of dissolved organics in potable water supply is aesthetically undesirable. Apart from imparting colour, taste and odour to treated water, it is also potentially hazardous to health. Two types of coconut shell derived activated carbon, KI-6070 and KI8085, provided by Kekwa Indah Sdn Bhd, were studied for the removal of dissolved organic compounds from Sungai Sireh Water Treatment Plant raw water, notorious of its high organic content. The respective external surface area of the KI-6070 and KI-8085 are approximately 277 m/g and 547 m2jg. The rate constant (~) for the KI-8085 was higher than that of the KI-6070, ranging between 30 and 70 %, for adsorbent dosages between 1.0 and 3.0 g. This was expected since the total surface area (specific and external surface areas) of the KI-8085 was higher than that of the KI-6070. The rate constant for the mass transfer was a function of the adsorbent dosage where both adsorbents indicated a proportional increase in the rate constant with increasing adsorbent dosage. The increasing dosage raised the intra particle diffusion rate constant (K.,) for both the KI-6070 and KI-8085, with the KI-8085 having a higher intra particle diffusion rate.